2016
DOI: 10.1111/1556-4029.13270
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Drug‐facilitated Sexual Assault—Xylazine Intoxication in a Child

Abstract: There are only a few cases of drug-facilitated sexual assaults on children reported in the literature so far. Here, a case of a four-year-old boy is presented. He was unconscious, and the accompanying adults reported that the child had been at a playground on his own. Returning home, he complained of having been stung and collapsed immediately. Urine and serum samples of the child were investigated. In the toxicological analysis, xylazine, a sedative and muscle relaxant used in animals, was detected. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The percentage recovery of xylazine reached its peak when the aqueous medium was adjusted to pH 11, suggesting that alkaline conditions are preferred. The preferred pH adjustment has been reported to be alkaline conditions of pH 9.5 [52] and pH 9 [13] before xylazine extraction. Nimetazepam was best extracted when the spiked sample had a pH of less than 10.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage recovery of xylazine reached its peak when the aqueous medium was adjusted to pH 11, suggesting that alkaline conditions are preferred. The preferred pH adjustment has been reported to be alkaline conditions of pH 9.5 [52] and pH 9 [13] before xylazine extraction. Nimetazepam was best extracted when the spiked sample had a pH of less than 10.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage recovery of xylazine reached its peak when the aqueous medium was adjusted to pH 11, suggesting that alkaline conditions are preferred. The preferred pH adjustment has been reported to be alkaline conditions of pH 9.5 [52] and pH 9 [13] In a study on the extraction of nimetazepam from vapes using LLE, a higher recovery percentage was achieved when the samples were in neutral conditions followed by acidic conditions, and the lowest was achieved under basic conditions [52]. To achieve optimum recoveries for all substances investigated in this study, the beverage samples were adjusted to pH 10 prior to the VADLLME procedure.…”
Section: Effects Of Phmentioning
confidence: 98%
See 1 more Smart Citation
“…A semi-structured interview reported that drug addicts who took xylazine and heroin together experienced a "high" sensation that could not result from consuming either drug alone (46). However, this combination was also reported to be potentially life-(GHB), ketamine, diazepam, and benzodiazepine (65) are common substances associated with DFC; however, xylazine was recently identified (16,17,66,67).…”
Section: Adulterant To Other Drugsmentioning
confidence: 99%
“…Drinks spiked with xylazine have been used to render elderly victims' unconscious before a robbery (17). An attempted sexual abuse case of a four-year-old boy, who involved the use of xylazine, was also reported, exemplifying the need for precautionary actions by the law enforcement authorities (66).…”
Section: Adulterant To Other Drugsmentioning
confidence: 99%